New occurrences of the White River Ash (east lobe) in Subarctic Canada and utility for estimating freshwater reservoir effect in lake sediment archives - Patterson, R. Timothy; Crann, Carley A.; Cutts, Jamie A.; Courtney Mustaphi, Colin J.; Nasser, Nawaf A.; Macumber, Andrew L.; Galloway, Jennifer M.; Swindles, Graeme T.; Falck, Hendrik (Palaeogeography, Palaeoclimatology, Palaeoecology, 2017)
The freshwater reservoir effect (FRE) in the Canadian Subarctic complicates development of high-resolution age-depth models based on radiocarbon dates from lake sediments. Volcanic ashfall layers (tephras) provide chronostratigraphic markers that can be used to estimate age offsets. We describe the first recorded occurrence of a visible tephra in a lacustrine sequence in the central Northwest Territories. The tephra, observed in Pocket Lake, near Yellowknife, is geochemically and stratigraphically attributed to the White River Ash east lobe (WRAe; 833–850 CE; 1117–1100 cal BP), which originated from an eruption of Mount Churchill, Alaska. We also observed the WRAe as a cryptotephra in Bridge Lake, 130 km to the NE, suggesting that records of this tephra are potentially widespread in CNT lakes. The identification of this tephra presents opportunities for use of the WRAe as a dating tool in the region and to quantify the magnitude of the FRE in order to correct radiocarbon age-depth models. Two well-dated sediment cores from Pocket Lake, containing a visible WRAe record, indicate a FRE of ~ 200 years at the time of the ash deposition, which matches closely with the estimated FRE of ~ 245 years at the lake sediment-water interface. Although additional results from other lakes in the region are required, this finding implies that FRE estimates for the late Holocene in the region, may be based either on down-core WRAe/radiocarbon age model offsets, or on radiocarbon dates obtained from the sediment-water interface.